New Mexico heritage - Paine, Lauran (Thorndike Press Thorndike, Maine, 1987)
Someone shoots Maria Antonia, the heir to Lord Land, at the funeral of its owner, and the doctor who saves her falls in love.
60866
Keywords: Large type books; Western stories